Five fall into adventure - Blyton, Enid; Soper, Eileen Alice (Hodder Children's London, 1997)
"George and Timmy the dog have disappeared -- and somebody has broken into Kirrin Cottage! The Famous Five are sure there's a connection -- but how can they solve the mystery when there are three of them?"--Page 4 of cover